2015
DOI: 10.1080/01930826.2015.1085232
|View full text |Cite
|
Sign up to set email alerts
|

From the Ground Up: Creating a Sustainable Library Outreach Program for International Students

Abstract: In spring 2014, the Henry Madden Library at Fresno State implemented an outreach program for incoming international students, consisting of a campus orientation presentation, library orientation and tours, information literacy workshops, and international peer advisor training. Assessment as a result of the program has shown a high level of use of help services among international students, as well as modestly higher use of several services and resources amongst students who attended the library orientation. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In order to connect with new and underserved campus populations, academic libraries are increasingly turning to outreach. Libraries are using outreach to engage with underserved patron populations (Helton 2010;Mathuews and Lewis 2017;Rutledge and LeMire 2016;Walter 2005) as well as other unique populations such as first-year students (Currie 2009;Collins and Dodsworth 2011), international students (Langer and Kubo 2015;Li, McDowell, and Wang 2016), and distance education students (Holloway 2011;Ziegler 2017). Libraries frequently report collaborating on outreach activities with campus units such as student services (Crowe 2010;Love and Edwards 2009;Ursin Cummings 2007), student organizations (Engle 2011), and academic departments (Cannady, King, and Blendinger 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to connect with new and underserved campus populations, academic libraries are increasingly turning to outreach. Libraries are using outreach to engage with underserved patron populations (Helton 2010;Mathuews and Lewis 2017;Rutledge and LeMire 2016;Walter 2005) as well as other unique populations such as first-year students (Currie 2009;Collins and Dodsworth 2011), international students (Langer and Kubo 2015;Li, McDowell, and Wang 2016), and distance education students (Holloway 2011;Ziegler 2017). Libraries frequently report collaborating on outreach activities with campus units such as student services (Crowe 2010;Love and Edwards 2009;Ursin Cummings 2007), student organizations (Engle 2011), and academic departments (Cannady, King, and Blendinger 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One method for ensuring that international students' needs are being continually reevaluated and prioritized is having an international student librarian. Langer and Kubo (2015) stated that such a librarian may "help facilitate communication as the single point person of the library, increase the awareness of international students' unmet needs, improve library services, programs, and collections for these students, and enhance the reputation of the library" (p. 607). Indeed, Gale (2006) was one such international student librarian who devised an action plan that strove to address common issues such as language barriers, unawareness of services and events, and cultural barriers.…”
Section: International Student Librarianmentioning
confidence: 99%
“…As events are held, data should be routinely gathered to maintain an accurate understanding of international students' needs, as demographics may change and responses to outreach may vary. Langer and Kubo (2015) surveyed international students' responses to outreach events. Their data revealed that reaching international students within the first few weeks was the most effective way for them to increase awareness and usage of the academic library and its services at Fresno State University.…”
Section: Data Collectionmentioning
confidence: 99%
“…For example, Flynn (2017) tracked attendance and collected feedback forms to evaluate the success of finals week outreach activities, and Vanden Elzen and Roush (2013) supplemented their observational assessment with a survey. Langer & Kubo (2015) used a combination of attendance tracking, a survey, and anecdotal feedback to assess their library's international student outreach program. Sclippa (2017) tracked attendance numbers, social media views, and survey results in order to gauge both event reach and potential areas for improvement.…”
Section: Literature Reviewmentioning
confidence: 99%